Perancangan Expert System untuk Menentukan Lokasi PPL pada Program Pendidikan Teknik Informatika dan Komputer UIN Sjech M.Djamil Djambek Bukitinggi - Marselino Syahputra; Liza Efriyanti; Riri Okra; Sarwo Derta (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The Field Experience Practice (PPL) is a key component of the Information Technology and Computer Education program at UIN SMDD BKT, designed to provide students with direct teaching experience and opportunities to apply classroom knowledge in real contexts. However, assigning suitable PPL locations can be challenging as various factors must be considered to match student abilities and conditions. This study develops an expert system using the Sugeno-type Fuzzy Logic method to assist in determining PPL placements objectively. The system evaluates four main indicators: students’ residence, microteaching scores, religious scores, and practice scores. After development, the system underwent validity, practicality, and effectiveness testing. The results showed a validity score of 0.9, indicating very high reliability; a practicality score of 0.78, showing ease of use; and an effectiveness score of 0.76, confirming the system’s ability to support decision-making in PPL placement. These findings demonstrate that the expert system is valid, practical, and effective, making it a reliable tool for assigning students to appropriate teaching locations. Consequently, the system is expected to enhance the efficiency and accuracy of the placement process by ensuring that students are positioned in environments aligned with the established criteria.